service innovation of chinese banks in UK - zhang, yifan(yf) (2011)
In modern competitive business world, once products or services lose their competitive advantages, service innovation quickly becomes another alternative and influencing way to achieve constant growth and profitability. (Berry et al. 2006). Therefore, this paper studies service innovation of Chinese banks in UK as valuable research objects and it mainly aims to explore factors that influence service innovation performances of banks and interactive relationships of those factors within or outside organizations. Although there are many previous reviews of relative studies, service innovation in financial organizations still has some gaps to fill, let alone when research objects are extremely particular and characteristic like Chinese banks in UK.